SONG (NDAWI) OF LANI TRIBE TO DEVELOP CONGREGATIONS’ INTEREST IN WORSHIP AT LOME BAPTIST CHURCH, LANI JAYA REGENCY - Noribena Wenda; Napius Kogoya (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The church is a gathering place for people who believe in Jesus Christ to praise and to glorify Him. Song is part one of the His followers to praise and glorify Him. The purpose of the study was 1) to determine the influence of song (Ndawi) Lani ethnic in developing their interest at the Lome Baptist Church. 2) to determine the factors that influence the congregation's interest in worshiping at the Lome Baptist Church. The researcher used a qualitative approach. The qualitative approach was chosen because the main focus of the study was to understand the social phenomena related to the song (Ndawi) from the Lani tribe. The population of this study was the entire Lome Baptist Church around aged 18-25 years and the sampel used was 15 people. The data collection techniques used were interviews and observations. The data analysis techniques were identification, classification, and drawing conclusions. The results shows that there are 13 parts, which are divided into (Ayi awu togon uwa iya wua togon uwa) wonderful God wonderful God, (Yetut awuri inom uwa Kritut awuri inom wua) Jesus is with his disciples, Christ is with his disciples, (Purom paga logoner wua taitom paga logoner wua) Living on the Mount of Olives, (Tamban eggwi wonoggwime wua) He is praying, (Ala yoggwi wonoggwime wua) He is asking for power from Him, (Yetut ogoma wagaggerak wua) The Spirit of Jesus came to take a ride, (Wiya pogom wagaggerak wua) He is coming like the wind, (Togi pogom wagaggerak wua) He is coming to brood on the snow, (Awuri aggo inikime wua) He is entering the hearts of His disciples, (Orewi aggo inikime wua) He is entering the hearts of His friends, (Enggi taa ndi’nduk eregerak wua) He is fulfilling in the heart, (Iyok taa ndi'nduk eremobil wua) He is soak the feet in the heart, (Ayii awu togon wua Iya wua togon wua) Wonderful God, miraculous God.